Testotoxicosis with iron deficiency anemia: A case report - Sarvodey, Shyam; SN, Mothi; Darla, B Harish; M, Manini; BR, Srirama; Darla, H Tanishka (Indian Journal of Child Health, 2022)
Testotoxicosis is an autosomal dominant disorder causing early-onset peripheral precocious puberty in boys. This condition is predominantly caused by an activating mutation in the luteinizing hormone receptor (LHR) gene, which causes constitutive activation of the LHR, stimulating testosterone secretion in Leydig cells, despite suppression of luteinizing hormone. We are presenting a case report of a 2.6-year-old male child, who is a known case of Global developmental delay and spastic cerebral palsy. He presented with pubic hair development and penile enlargement as noticed by his mother at 10 months of age along with masculine features such as premature virilization of voice, acne, and breath holding spells. On further evaluation, he was diagnosed to have a rare genetic/heredofamilial disorder of testotoxicosis with iron deficiency anemia. The treatment consists of reducing hyperandrogenism in the children (sexual maturation, stature), with ketoconazole or a combination of antiandrogens and aromatase inhibitors. However, unfortunately, the treatment is not highly successful. Further, experience and controlled clinical trials are necessary to clarify the efficacy of combination therapy. Successful treatment can only be evaluated through long-term follow-up of these patients. The presenting case did not come for follow-up after the diagnosis and initial treatment advice.